Cobalt Nanoparticles/Black Phosphorus Nanosheets: An Efficient Catalyst for Electrochemical Oxygen Evolution - Shi, Fangbing (Adv Sci (Weinh), 2018)
Black phosphorus (BP) nanosheet (NS) is an emerging oxygen evolution reaction (OER) electrocatalyst with both high conductivity and abundant active sites. However, its ultrathin structure suffers instability because of the lone pair electrons exposed at the surface, which badly restricts durability for achieving long‐term OER catalysis. Herein, a facile solvothermal reduction route is designed to fabricate Co/BP NSs hybrid electrocatalyst by in situ growth of cobalt nanoparticles on BP NSs. Notably, electronic structure engineering of Co/BP NSs catalyst is observed by electron migration from BP to Co due to the higher Fermi level of BP than that of Co. Because of the preferential migration of the active lone pairs from the defect of BP NSs, the stability and high hole mobility can be effectively retained. Consequently, Co/BP NSs electrocatalyst exhibits outstanding OER performance, with an overpotential of 310 mV at 10 mA cm(−2), and excellent stability in alkaline media, indicating the potential for the alternatives of commercial IrO(2). This study provides insightful understanding into engineering electronic structure of BP NSs by fully utilizing defect and provides a new idea to design hybrid electrocatalysts.